Membangun Aplikasi Manajemen Mahasiswa Menggunakan React Vite dan Laravel - Abdillah , Athif Nur; Fakhriza , Naufal; Adritara , Muhammad Zaid Parhan; Saputra , Adji Setyawan; Faizzaki , Nurfaiq; Rosanti , Nurvelly; Ambo , Sitti Nurbaya; Risanty , Rita Dewi; Hendra , Hendra (Dedication : Jurnal Pengabdian Masyarakat, 2026)
Mastering modern full-stack technology is crucial, yet students often struggle to integrate frontend and backend systems using React Vite and Laravel. This community service program aims to bridge this gap through intensive training titled "Building Student Management Application Using React Vite and Laravel". Held online on January 6, 2026, the activity combined webinars and practical workshops attended by 38 participants. The program's effectiveness was evidenced by evaluation results showing an increase in participant competence, with average scores rising from 82.5 (pre-test) to 88.67 (post-test). Furthermore, feedback indicated a participant satisfaction rate of 96.8%. The final output was the participants' success in independently building a functional student management application.